Managing Immune Checkpoint-Blocking Antibody Side Effects - Michael A. Postow (2015)
Immune checkpoint-blocking antibodies that enhance the immune system's ability to fight cancer are becoming important components of treatment for patients with a variety of malignancies. Cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4) was the first immune checkpoint to be clinically targeted, and ipilimumab, an inhibitor of CTLA-4, was approved by the U.S. Food and Drug Administration (FDA) for patients with advanced melanoma. The programmed cell death-1 (PD-1) receptor and one of its ligands, PD-L1, more recently have shown great promise as therapeutic targets in a variety of malignancies. Nivolumab and pembrolizumab recently have been FDA- approved for patients with melanoma and additional approvals within this therapeutic class are expected. The use of anti-CTLA-4 and anti-PD-1/PD-L1 antibodies is associated with side effects known as immune-related adverse events (irAEs). Immune-related adverse events affect the dermatologic, gastrointestinal, hepatic, endocrine, and other organ systems. Temporary immunosuppression with corticosteroids, tumor necrosis factor-alpha antagonists, mycophenolate mofetil, or other agents can be effective treatment. This article describes the side-effect profile of the checkpoint-blocking antibodies that target CTLA-4 and PD-1/PD-L1 and provides suggestions on how to manage specific irAEs.